URGENSITAS PENGOPTIMALAN PERATURAN OTORITAS JASA KEUANGAN TERKAIT FINANSIAL TECHNOLOGY - Elisa Stefanie, (2021)
In the midst of the Covid-19 pandemic, the Investment Alert Task Force found 126 illegal fintechs that deliberately took advantage of the financial difficulties of some people during this pandemic. This proves that the existence of illegal fintech in Indonesia is not insignificant, the absence of special regulations regarding illegal fintech has resulted in the increasing number of illegal fintech entities in the community as well as the potential for shadow banking practices that can put the financial system at risk. From this background, the writer wants to answer two questions. First, the potential risk of shadow banking to the financial system. Second, the urgency of optimizing OJK regulations related to fintech. This study uses a normative legal research method (juridical normative) with a statutory approach (statute approach). The potential risk of shadow banking practices is the result of the absence of specific regulations governing shadow banking on fintech services, which so far have only been limited to POJK. OJK policy optimization related to fintech is something that must be done immediately based on physiological, sociological and juridical aspects. My advice is that the OJK should immediately issue a regulation or optimize POJK Number 77 of 2016 related to fintech so that it can specifically regulate illegal fintech and shadow banking, starting from illegal fintech law enforcement, following up on shadow banking practices and strict sanctions that can have a deterrent effect on fintech is illegal. Keywords: Urgency, Shadow Banking, Illegal Fintech.